Depressive symptomatology in men receiving androgen deprivation therapy for prostate cancer: a controlled comparison. Issue 4 (13th June 2014) - Lee, Morgan; Jim, Heather S.; Fishman, Mayer; Zachariah, Babu; Heysek, Randy; Biagioli, Matthew; Jacobsen, Paul B.
Abstract Objective Prostate cancer patients who receive androgen deprivation therapy (ADT) often experience many physical and psychological side effects. ADT may be associated with increased risk for depression, but the relationship between ADT and depression is not fully understood. This study used a longitudinal design to assess depressive symptomatology in patients receiving ADT compared with two groups of matched controls. Methods Participants were men initiating ADT treatment (ADT+ group; n = 61) and their matched controls: prostate cancer patients treated with radical prostatectomy (ADT− group; n = 61), and no‐cancer controls (CA− group; n = 61). Depressive symptomatology was assessed using the Center for Epidemiological Studies Depression Scale at ADT initiation and again 6 months later. Differences in depressive symptomatology and rates of clinically significant depressive symptomatology were analyzed between groups at each time point and within groups over time. Results Between baseline and follow‐up, ADT+ participants demonstrated increased depressive symptomatology and increased rates of clinically significant depressive symptomatology (ps < 0.05). ADT+ participants also reported greater depressive symptomatology than both control groups at follow‐up (ps < 0.001). Rates of clinically significant depressive symptomatology were higher in the ADT+ group than the ADT− and CA− groups at both time points (baseline: 28%, 5%, 12%; follow‐up: 39%, 9%, 11%). Conclusions Findings support the hypothesis that ADT administration yields increases in depression and suggest that the mechanism behind ADT's association with depression should be explored and that prostate cancer patients treated with ADT should receive particular focus in depression screening and intervention. Copyright © 2014 John Wiley & Sons, Ltd.